Prevalence of Association of Dietary Habits with Chronic Energy Deficiency in Ethnic Adult Punjabi Population - Brar, Amrit Pal Singh; Nagpal, Manisha; Sadana, Pooja; Sharma, Nishant; Brar, Deepinder Pal Singh; Kaur, Sandeep (Indian Journal of Community Health, 2024)
Background: Food is a basic thing without which, life is impossible. Without proper food, body will not thrive to its optimum potential and Chronic Energy Deficiency (CED) is the state, where there is a lack of food intake over a prolonged period of time. Aims & Objectives: To find the association of dietary habits with CED in ethnic Punjabi population. Methodology: The study was a cross-sectional study using simple random sampling technique. Taking the prevalence of CED as 30% in India, the sample size came out to be 336 but, 400 subjects were selected equally from rural and urban areas for convenience. Results: Subjects having lesser calorie intake than RDA, developed CED more 62(82.9%) than meeting RDA 13(17.1%). Subjects who skipped meals had higher CED rates. Pure vegetarians had higher rates of CED 71(93.4%) than non-vegetarians 5(6.6%). People consuming milk or milk products more than once daily developed lesser CED 1(1.3%) than those taking once daily 15(19.7%) and ones taking only once a week 60(79.0%). Conclusion: According to the study, persons with adequate calorie intake, who do not skip meals, take some kind of non-vegetarian food, and consume milk on daily basis have lesser tendency to develop CED.